Pengaruh Manajemen Laba Terhadap Nilai Perusahaan Di Moderasikan Kepemilikan Manajerial dan Komisaris Independen - Devih Anggraini; Emi Lestari Lestari (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2023)
This study aims to analyze the effect of earnings management on firm value with moderating variables of managerial ownership and independent commissioners. The sampled companies in this study are manufacturing sector companies specialized in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021. The research method is quantitative with secondary data obtained from the company's financial statements through the IDX website and the website of each company. This study sampling method is purposive with 112 data sample. The analysis method in this study uses descriptive test, classical assumption test, MRA regression test, and hypothesis testing. The application to test the data is SPSS 25. The research results obtained are that (1) Earnings Management has no effect on firm value. Moderating variable (2) Managerial Ownership cannot affect earnings management on firm value. Likewise, the moderating variable (3) Independent Commissioner cannot influence earnings management on firm value.